2018
DOI: 10.1080/17461391.2018.1424257
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between meeting of recommendations on physical activity for health and perceived work ability among white‐collar workers

Abstract: Meeting leisure-time physical activity recommendations (especially the criterion of vigorous physical activity) is significantly related to higher self-assessed ability to work among white-collar workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
(48 reference statements)
1
23
0
1
Order By: Relevance
“…Some studies have shown the significant relationship between physical activity and the ability to work. [29][30][31] Work ability can be defined as having the health, competence and relevant occupational virtues required for managing some kind of job, assuming that the work tasks are reasonable and that the work environment is acceptable. 32 Therefore, it should be noted that the concept of work ability is holistic and can be affected by various factors, such as, eg, work stressors, individual characteristics, and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the significant relationship between physical activity and the ability to work. [29][30][31] Work ability can be defined as having the health, competence and relevant occupational virtues required for managing some kind of job, assuming that the work tasks are reasonable and that the work environment is acceptable. 32 Therefore, it should be noted that the concept of work ability is holistic and can be affected by various factors, such as, eg, work stressors, individual characteristics, and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study presented a smaller but significant relationship between lower OPA levels and LTPA. Nawrocka et al ( 2017 ) found a relationship between achieving recommended LTPA levels and WAI among white-collar workers. In the present study, even though the majority of participants were blue-collar workers, our results indicated a similar relationship in the group that had the lowest OPA level.…”
Section: Discussionmentioning
confidence: 99%
“…LTPA and WAI within domains of OPA, is warranted. Previous studies have presented a strong positive association between the lack of vigorous LTPA and poor WAI (van den Berg et al 2009 ) and there has been relationship when achieving recommended LTPA levels and better WAI among sedentary workers (Nawrocka et al 2017 ). In addition, previous study found an association between high LTPA levels and better work ability in middle-aged workers with physically demanding jobs (Calatayud et al 2015 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since the physical activity of adults is highly significant for their proper social and individual functioning [28][29][30][31], it is necessary to undertake effective actions regarding individuals prone to hypokinesia, i.e. people without a steady income, low income, no money savings, and debt.…”
Section: Discussionmentioning
confidence: 99%